2002
DOI: 10.1007/s00405-001-0442-x
|View full text |Cite
|
Sign up to set email alerts
|

A giant pyogenic granuloma in the nasal cavity caused by nasal packing

Abstract: Pyogenic granuloma is a benign, rapidly growing hemorrhagic lesion of unknown origin. This disorder, however, is obscure to many rhinologists, because the nose is a relatively rare location for the lesion. In the practice of otorhinolaryngology, nasal packing is a very common procedure for nasal bleeding and postoperative hemostasis. However, few pyogenic granulomas occurring from nasal packing have been reported in the literature. A 56-year-old man underwent nasal packing with vaseline gauze because of nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 7 publications
1
52
1
3
Order By: Relevance
“…The ulcerative area is composed of neutrophilic infiltrates and irregular dilation of blood vessels, which may undergo secondary nonspecific changes, including stromal edema, inflammation, and a granulation tissue reaction. 4,5 Nasal LCH may develop at any age but is more frequent in the third and fourth decades and in females, 3,4,7,8,11 though our study showed a slight male predominance. LCH usually manifests as recurrent unilateral epistaxis, nasal obstruction, and purulent nasal discharge.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The ulcerative area is composed of neutrophilic infiltrates and irregular dilation of blood vessels, which may undergo secondary nonspecific changes, including stromal edema, inflammation, and a granulation tissue reaction. 4,5 Nasal LCH may develop at any age but is more frequent in the third and fourth decades and in females, 3,4,7,8,11 though our study showed a slight male predominance. LCH usually manifests as recurrent unilateral epistaxis, nasal obstruction, and purulent nasal discharge.…”
Section: Discussioncontrasting
confidence: 48%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] LCH is now accepted as the preferred nomenclature because it best represents the true nature of the lesion, which consists of capillaries arranged in lobules and separated by an edematous fibroblastic stroma infiltrated by inflammatory cells. 1,4,12 LCH usually originates from the vascular tissue of the skin, mucosa, muscle, gland, and bone.…”
mentioning
confidence: 99%
“…When it is seen in the nasal cavity, LCH mostly locates on the anterior portion of nasal septum (Little's area), less frequently on anterior side of inferior turbinate. 3,4 In this case LCH was arising from the lateral nasal wall of left nasal cavity. The most common presenting symptom of LCH of the nasal cavity is bleeding and/or obstructive symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…There is no intercommunication of vascular spaces or cytological atypia. [1][2] Usually clinical findings, imaging methods and biopsy lead to diagnosis. The advent of endoscopy has eased the approach for diagnosis and treatment of such nasal masses which vary in site, size and degree of vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In the nasal cavity, it commonly locates on the anterior portion of nasal septum (Little's area), followed by lateral wall, vestibule and middle turbinates. [1] [2] LCH occurs at all ages, more often in the third decade, and is commoner in females. In the pediatric age group, it commonly affects males.…”
Section: Introductionmentioning
confidence: 99%